Development of Interactive Virtual Reality Learning Media Based on the RADEC Model for Science Learning in Elementary Schools - Izzan Muhammad Furkan; Risda Amini; Muhammadi Muhammadi; Rayendra Rayendra (Journal of Educational Sciences, 2026)
This study was motivated by low student engagement, limited use of innovative learning media, and students’ difficulties in understanding abstract concepts, particularly the human digestive system in Integrated Science and Social Studies learning at the elementary school level. The study aimed to develop an interactive Virtual Reality learning medium based on the RADEC (Read, Answer, Discuss, Explain, Create) approach for fifth-grade students. The research employed a Research and Development design using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed VR-based RADEC medium was validated by material, language, and media experts, achieving a validity score of 92.66%, categorized as highly valid. Practicality testing conducted in four elementary schools showed very high practicality, with student and teacher response scores of 93.8% and 96.2%, respectively. Effectiveness testing using pre-test and post-test results demonstrated a significant improvement in student learning outcomes, indicated by an average N-Gain score of 0.76, classified as high. These findings indicate that the developed VR-based RADEC interactive learning medium is valid, practical, and effective. Furthermore, it supports the implementation of the Merdeka Curriculum by providing realistic, engaging learning experiences that enhance student motivation and learning achievement.